The development of new electrophoretic and staining procedures for the detection on zymograms of some enzymes from the human brain, liver and placenta - Teng, Yao Sheng; Tan, Soon Guan (1977)
New methods have been developed for the electrophorenis and staining of the following enzymes:- peroxidase and monoamine oxidase from the placenta, -hydroxyacid oxidase from the placenta and liver,uridine diphosphatase from the liver and fructose-1,6-diphosphatase from the brain and liver. These enzymes have not yet been previously detected and studied from these human organs by the zymogram techniques. The ability to detect these enzymes by the zymogram technique will enable to study of their genetic controls. It is often the case that different proteins which posses the same enzymatic activity,are expressed differentially in different tissues and organs of the same organism. Hence these new procedures which enable the detection,by the zymogram technique,of several enzymes from several human sources from which they have not been studied genetically before can aid in the advancement of the study of biochemical and population genetics,the mechanism of the control of differential gene activity and evolution at the molecular level.